Theoretical Issues of Property Liability for Damage Caused to Natural Objects of Ownership (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article analyzes the theoretical issues of property liability for damage caused to natural objects of ownership. Particular attention is paid to the definition of such terms as: “property liability”, “environmental harm”, “economic harm”, “classification of property liability for environmental harm”. The general and specific features of legislative acts of the Republic of Uzbekistan in the field of compensation for damage caused to natural objects of property rights are analyzed. The main shortcomings of the legislation in this area are identified, as well as conclusions and recommendations for improving land legislation in the field of property liability for environmental damage are formulated.